THE INFLUENCE OF ENGLISH LANGUAGE EXPOSURE MEDIA ON THE STUDENTS’ SPEAKING ABILITY: A PRE-EXPERIMENTAL STUDY ON GRADE XII IPS OF SMA SANTO FRANSISKUS ASISI PONTIANAK - Etna Gres; Eusabinus Bunau; Regina Regina (Wiralodra English Journal, 2024)
This research was conducted to find out whether English Language Exposure Media influence students’ speaking ability or not. This research also concentrated on utilizing different types of English language exposure media within the curriculum, including music videos, podcasts, and songs. All of the media were presented in English language to give them the exposure of the language. A pre-experimental design was utilized, incorporating a pre-test, post-test, and two treatment phases. Data were gathered using a measurement technique that involved a speaking test. The research findings revealed that the pre-test score averaged 54.60, while the post-test score averaged 78.33. The mean score difference between the pre-test and post-test was 25.73, indicating an improvement in students' speaking abilities following the treatments. The effect size (ES) was calculated to be 2.38, which is classified as a strong effect (ES > 1.00). The research demonstrated a substantial improvement in students' speaking ability, with a mean score increase from 54.60 to 78.33, indicating the effectiveness of English language exposure media. Future research could explore the long-term impact of English language exposure media on students' speaking skills. Additionally, examining the effectiveness of different types of media and their influence on various language skills would provide a more comprehensive understanding.